Penerapan Model Team Games Tournament Untuk Meningkatkan Motivasi Belajar PAI di SMPN 1 Takkalalla - Rahman, Muh Rifki; Syahid, Akhmad; Setiawati, Nur; Nurlaelah, Nurlaelah; Surani, Surani (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
Examining how the Team Games Tournament (TGT) learning paradigm might increase students' motivation to learn is the goal of this study. TGT is a cooperative learning approach that creates an engaging and dynamic learning environment by fusing group projects, instructional games, and competition activities. Classroom action research, or CAR, is the methodology used in this study. Students who had taken part in learning utilizing the TGT model were given learning motivation questionnaires as part of the data collection process. The data analysis's findings demonstrate that applying the TGT approach helps raise students' motivation for studying. This is demonstrated by the rise in motivation scores derived from the examined questionnaire data. As a result, the TGT model can be applied as a substitute for traditional teaching methods to boost students' willingness to learn, particularly in junior high school Islamic Religious Education courses.